Geochemical Investigation of Selected Elements in an Agricultural Soil: Case Study in Sumani Watershed West Sumatera in Indonesia - . Aflizar; . Muzakkir; Roni Afrizal; Muhammad Azadur Rahman (JOURNAL OF TROPICAL SOILS, 2016)
This paper presents the geochemical study of agricultural soil and river sediments along Sumani watershed, West Sumatra in Indonesia. We examined the distribution and abundances of 16 elements (Pb, Zn, Cu, Ni, Cr,V, Sr, Rb, Ce, Th, Zr, Si, Ti, Fe Ca, and P) in vegetable soil, sawah soil =and river sediment sample, to evaluate the factors controlling their abundances, possible sources, and environmental implications. Average concentrations of Pb, Zn, Cu, Ni, Cr,V, Sr, Rb, Ce, Th, Zr at vegetable (1) soil were 38, 88.3, 38.7, 3, 8, 101, 96, 98, 87, 31 and 218 mg kg-1 , 26, 39.05, 8.8, 13.5, 31, 231.5, 37, 19, 78, 16 and 303.5 mg kg-1 at sawah soil (3, 4) and 30, 61.6, 35.7, 9, 22, 294, 65, 12, 78, 14 and 232 mg kg-1 at river sediment (2), respectively. The concentration of Pb, Rb, Th and Zr at upland vegetables, V and Zr at sawah soil and river sediment were mostly two time Sumatra BCSCST or BCC in several samples. Enrichment factor values showed low to moderate enrichment of Pb, Zn, Cu, Rb, Ce and Zr, whereas Th showed significant contamination at vegetables soil, suggesting contributions from anthropogenic sources. Anthropogenic contributions of most metals mainly originate from natural processes. However, Pb, Ce, Th and Zr ranges of 527–108, 41-89, 66-117 and 35-100%, respectively, at Vegetable and sawah soil and river sediment confirm their anthropogenic contribution. Factor analysis and correlation matrices suggested that elevated metal concentrations at agricultural soil in Sumaniwatershed might be controlled by pH, CEC, Fe-oxy-hydroxides. Deposition of metals at vegetable and sawah soil and river sediment might be controlled by non-ferrous metal (i.e., aluminosilicates), sediment grain size, or source rock composition (andesite, alluvial fan, undifferentiated volcanic material, granite and gneiss).Keyword: Agricultural soil, anthropogenic activities, enrichment factor, metals source, river sediment, watershed trace [How to Cite: Aflizar, Muzakkir, R Afrizal and MA Rahman. 2016. Geochemical Investigation of Selected Elements in an Agricultural Soil: Case Study in Sumani Watershed West Sumatera in Indonesia. J Trop Soils 21: 49-66. Doi: 10.5400/jts.2016.21.1.49]